Design of a Hierarchical Meso/Macroporous Zeolite‐Supported Cobalt Catalyst for the Enhanced Direct Synthesis of Isoparaffins from Syngas. Issue 4 (30th January 2015) - Lin, Qihang; Yang, Guohui; Chen, Qingjun; Fan, Ronggang; Yoneyama, Yoshiharu; Wan, Huilin; Tsubaki, Noritatsu
Abstract A hierarchical meso/macroporous zeolite‐supported Co catalyst (Co/ASB) was designed and employed for the direct synthesis of isoparaffins. The hierarchical porous zeolite (ASB) was developed by a steam‐assisted crystallization method using alumina‐modified meso/macroporous silica as the precursor. Structural characterization indicated that the as‐synthesized ASB exhibited nanosized β‐zeolite crystallites and a hierarchical meso/macroporous structure. The activity of the Co/ASB catalyst was much higher than that of conventional Co catalysts supported on SiO2 (Co/SiO2) and H‐β‐zeolite (Co/B). A high isoparaffins selectivity of 30.5 % was obtained from Co/ASB because of the hydrocracking/isomerization of long‐chain hydrocarbons at the strong acidic sites of the β‐zeolite. Furthermore, as a result of the fast diffusion of syngas in the unique hierarchical pores, the methane selectivity of Co/ASB was lower than that of Co/B.